Psychosemantic approach as the basis for the algorithmization technology of processing educational information - Elena V. Tsupikova; Margarita V. Tsyguleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
An ability to improve the professional level, need for self-development and self education is called to be one of the essential qualities of a modern specialist irrespective of the professional sphere. Such an activity requires intellectual and psychological mobility, wish to obtain and process huge amount of new and complex information, ability to apply new knowledge to correct and modify the existing system of experience and activity. In the evolution of the information society, self-development and self education are at the top of the soft skills list; therefore formation of a new thinking style is becoming the most important task of teaching. The aim of the paper is to present an argument for introducing some elements of algorithmization of work with student texts based on the psychosemantic approach. Semantic principles (matching of logical and linguistic categories, considering the text from the inner and outer speech, considering the text as cognitive and communicative essence; differentiation between the meaning and sense as between the semantics of the outer speech and the semantics of thinking; identification of semantic relationships between information elements, etc.), psychological and pedagogical principles (self-reflection support of learning activity; self-motivation due to determining usefulness and applicability of information; self-organization of students while creating their own algorithms of learning activity, etc.), and psycholinguistic principles (building logical supporting schemes, analogues of universal subject codes; semantic evaluation of the quantitative and qualitative characteristics of information, etc.)of work with scientific and educational profession-oriented information are described and correlated with the learning content and mechanisms of students verbal and cognitive activity. Psycholinguistic, semantic and organizational competences are identified, with a set of knowledge, skills and abilities for each of them being defined. The authors suggest a technology of algorithmization of students work with the professionally-oriented text information on the basis of a psychosemantic approach. The purpose of the algorithmization is to accelerate students work and improve the quality of information acquisition.